ALTERNATIVE FEED OF SEAWEED MEAL CAULERPA RACEMOSE ON THE GROWTH OF VANAME SHRIMP (Penaeus vannamei) - Dewi Yuniati; Muh. Fadli; Darsiani Darsiani; Zulfiani Zulfiani; Nurfadillah Nurfadillah; Shobrina Shobrina (Jurnal Perikanan Unram, 2024)
This study aims to determine the effect of seaweed meal Caulerpa racemose on the growth and survival rate of vaname shrimp (Litopenaeus vannamei) fry. The shrimp reared for 30 days at Balai Benih Ikan Pantai (BBIP) Poniang. This study used a Complete Randomized Design with 4 treatments and 3 replication.  The dose of seaweed added to the feed is 0% in treatment A or control, 5% in treatment B, 15% in treatment C and 25% in treatment D. The density of the shrimp was 3 fishes/L. The shrimp feed 3 times daily at 07.00, 14.00, and 21.00 WITA with feeding rate of 5% of body weight. Data analysis was performed using SPSS 22.00 software. The parameters tested included absolute weight growth, specific growth rate, and survival rate. The results showed that the utilization of seaweed meal had no real effect (p>0.05) on absolute weight growth, specific growth rate, and survival rate in vaname shrimp fry.